PENGARUH MOTIVASI, KOMITMEN KERJA, DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT INDOMARCO PRISMATAMA DC TANGERANG 2 BITUNG KABUPATEN TANGERANG - Deci Rahakbauw, Oktovina; Nandika Setiawan, Halfian (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2023)
ABSTRACT This study aims to analyze the influence of Motivation, Work Commitment, and Work Environment on Employee Productivity at PT Indomarco Prismatama DC Tangerang 2 Bitung, Tangerang Regency partially and simultaneously. This study used a sample of 50 employees with data collection techniques using a questionnaire. The test results of this study show that multiple linear regression analysis has the equation Y = 17.086 + 0.300X1 + 0.123X2 + 0.204X3 . The test results for the coefficient of determination (R2) Adjusted R Square have a value of 0.443 or 44.3%, so it is concluded that 47.7% of employee productivity is influenced by the three independent variables (motivation, work commitment, and work environment). While the remaining 55.7% is influenced by factors outside the research. The results of the t test show that the motivation variable (X1) on employee productivity (Y) has a t count value of 3.379> t table 2.012 with a significance level of 0.01 <0.05, the work commitment variable (X2) on employee productivity (Y) has a value t count 1.048 < t table 2.012 with a significance level of 0.300 <0.05, and the work environment variable (X3) on employee productivity (Y) has a t count value of 2.087 > t table 2.012 with a significance level of 0.042 <0.05. Then the motivational variable (X1), communication variable (X2), work environment variable (X3) have a partial effect on employee productivity (Y). The results of the F test show F count 13.999 > F table 2.57 with a significance level value of 0.000 <0.05, then motivation, work commitment, and work environment simultaneously influence the productivity of employees of PT Indomarco Prismatama DC Tangerang 2 Bitung Tangerang Regency.